1999
DOI: 10.1002/(sici)1099-1395(199909)12:9<713::aid-poc182>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of solvent mixtures: preferential solvation of chemical probes in binary solvent mixtures of polar hydrogen-bond acceptor solvents with polychlorinated co-solvents

Abstract: The use of chemical probes for the characterization of chemical properties is explored for aprotic binary solvent mixtures. The solvatochromic indicators N,N-diethyl-4-nitroaniline, 4-nitroanisole, 4-nitroaniline and 4-nitrophenol were used to characterize binary solvent mixtures of a polar aprotic hydrogen-bond acceptor solvent (ethyl acetate, acetonitrile and dimethyl sulfoxide) with a polychlorinated hydrogen-bond donor solvent (chloroform or dichloromethane). The solvent parameters p*, a and b of the binar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Examination of the literature revealed that the effects of structure on S N Ar2 reactions have largely been reported 9–23. However, only very few attempts have been made to study on the effect of solvent on such reactions in a more systematic manner 24–30. Hence, in this article, the reaction of few parasubsutituted anilines with 2‐bromo‐5‐nitropyridine and with 2‐chloro‐5‐nitropyridine in dimethylsulfoxide (DMSO)/acetonitrile (AcN) (both polar, aprotic, Hydrogen Bond Acceptor, PAHBA solvents) mixtures of varying compositions has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of the literature revealed that the effects of structure on S N Ar2 reactions have largely been reported 9–23. However, only very few attempts have been made to study on the effect of solvent on such reactions in a more systematic manner 24–30. Hence, in this article, the reaction of few parasubsutituted anilines with 2‐bromo‐5‐nitropyridine and with 2‐chloro‐5‐nitropyridine in dimethylsulfoxide (DMSO)/acetonitrile (AcN) (both polar, aprotic, Hydrogen Bond Acceptor, PAHBA solvents) mixtures of varying compositions has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The n dependence of K dim,n could, therefore, be expressed by Eq. (11) K dim,n = K cyc dim (1 − n + 1.86n) 4 (1 − n + 6.91n) 4 (11) where the numerator represents the contribution of four solvation sites of the dimer and the denominator represents that arising from four solvation sites of the two monomeric entities. Substitution of appropriate n values in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…and the specific solute-solvent interactions (hydrogen bonding). Despite the many theoretical [1,2] as well as experimental [3][4][5] approaches reported to elucidate this phenomenon, the general mechanisms of preferential solvation in mixed solvents has not yet been completely clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In other cases, both constituents of the solvent mixture can solvate a probe molecule as a different entity which provides a completely different solvation environment around the solute molecule causing to show a significant change of a particular property (solvation in the present study) from its bulk counterparts and this effect is known as synergetic effect . The experimental and theoretical tools have been used in a great deal to understand the preferential solvation as well as synergetic behavior of the solvent mixtures . Several different spectroscopic techniques such as UV‐Vis, NMR, vibrational spectroscopy, solvation dynamics, two dimensional infrared techniques have been used to understand the behavior of solvent mixtures as these techniques have the capability to provide the quantitative information about the solute‐solvent interaction as well as hydrogen bond network present in solvent mixtures.…”
Section: Introductionmentioning
confidence: 96%